Peningkatan Pengetahuan Petani Madu tentang Pemasaran Digital melalui Pengembangan Website E-Commerce KTH Sadar Tani Muda Desa Bojongmurni - Pesalmen Butarbutar; Noviana Yuliawati; Arina Destyana; Bima Yeremia Hutahaean; Muhammad Sidiq Haryadi Sutisna; Ribka Wahyuni Simarmata; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital marketing has become a crucial solution for honey farmers to boost sales and expand their market reach. This community service activity aims to enhance the knowledge of honey farmers in the KTH Sadar Tani Muda group regarding the use of e-commerce websites for honey product marketing. The methods employed include training, mentoring, and the development of a simple e-commerce platform-based website. The results indicate a significant improvement in farmers' understanding of digital marketing benefits, e-commerce features, and independent product content management. Additionally, the developed website has enhanced the online visibility of honey products. The impact of this initiative extends beyond increased sales, opening broader marketing opportunities. This activity is expected to serve as a model for other farmer groups in adopting digital technology for business development